1982
DOI: 10.1256/smsqj.45808
|View full text |Cite
|
Sign up to set email alerts
|

A diffusive model of the turbulent mixing of dry and cloudy air

Abstract: SUMMARYA model is presented of the turbulent mixing between a sphere of droplet-free air (saturated or undersaturated) and a spherical volume of cloud within which it is embedded. The rates of equalization of supersaturation, temperature and liquid water are examined as functions of the turbulent energy dissipation rate, the dimensions of the interacting volumes, the drop-size distribution in the cloud and other parameters. Spectral changes resulting from the mixing conform closely with those predicted by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 1 publication
(4 reference statements)
0
13
0
Order By: Relevance
“…Note that time-dependent mixing was also considered in several studies (e.g., Baker et al, 1980;Baker and Latham, 1982;Jeffery and Reisner, 2006;Krueger et al, 1997;Kumar et al, 2012) using different approaches and numerical models. These studies, however, do not contain analysis on non-dimensional diffusionevaporation equation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that time-dependent mixing was also considered in several studies (e.g., Baker et al, 1980;Baker and Latham, 1982;Jeffery and Reisner, 2006;Krueger et al, 1997;Kumar et al, 2012) using different approaches and numerical models. These studies, however, do not contain analysis on non-dimensional diffusionevaporation equation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, inhomogeneous mixing is investigated based on the analysis and solution of a 1-D diffusion-evaporation equation. To our knowledge, the idea of using a diffusive model of turbulent mixing to describe the mixing process was first proposed by Baker and Latham (1982). A diffusion-evaporation equation was also analyzed by Jeffery and Reisner (2006).…”
Section: The Main Concept and The Basic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid water fluxes are important (Randall, 1980a), and may be obtainable directly from aircraft measurements as well as remotely from millimeter-wavelength doppler radar. A related issue is the role of entrainment in determining the cloud droplet distribution (Baker and Latham, 1982). For this, microphysical measurements, in addition to dynamic and thermodynamic measurements, are needed.…”
Section: What Determines the Entrainment Rate?mentioning
confidence: 99%
“…Turbulent mixing at cloud edges and cloud tops accompanied by phase transitions has been the focus of numerous studies, beginning with the pioneering works of Baker and Latham (1979), Baker et al (1980), Blyth et al (1980) and Baker and Latham (1982). Laboratory experiments by Latham and Reed (1977) showed that after mixing with subsaturated air some droplets completely evaporate while others remain unchanged.…”
Section: Introductionmentioning
confidence: 99%